1999
DOI: 10.1042/cs19980255
|View full text |Cite
|
Sign up to set email alerts
|

Altered small artery morphology and reactivity in critical limb ischaemia

Abstract: Although the pathophysiology of critical limb ischaemia is poorly understood, there is evidence that the condition of the small arteries may determine the outcome of revascularization procedures. This study was designed to investigate the effects of critical limb ischaemia on the structure and function of the small arteries in the leg. Small arteries (<500 microm) from proximal (non-ischaemic) and distal (ischaemic) sites were obtained from patients undergoing bypass surgery for critical limb ischaemia and mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The development of smooth muscle dysfunction as a result of 5 weeks of chronic ischaemia in the rat is supported by attenuation of dilation to both these agonists. Hillier et al [9]also demonstrated attenuated SNP responses due to chronic ischaemia in human leg arteries, while Thomas et al [32]showed attenuation of AD vasoactivity in skeletal muscle arterioles of chronic heart failure rats. These effects could also be explained by dysfunction of smooth muscle receptors or second messenger systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of smooth muscle dysfunction as a result of 5 weeks of chronic ischaemia in the rat is supported by attenuation of dilation to both these agonists. Hillier et al [9]also demonstrated attenuated SNP responses due to chronic ischaemia in human leg arteries, while Thomas et al [32]showed attenuation of AD vasoactivity in skeletal muscle arterioles of chronic heart failure rats. These effects could also be explained by dysfunction of smooth muscle receptors or second messenger systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As α 2 -receptors are more prevalent than α 1 -receptors on terminal arterioles in skeletal muscle [30], it may be the former that are affected. Hillier et al [9]reported smaller constrictor responses to NA in arteries of 250–300 µm internal diameter taken from the subcutaneous fat of ischaemic calf muscles in patients compared with control vessels but did not see any pathology in the vascular smooth muscle. These vessels, however, may not have experienced the same ischaemia as those of the deeper muscular tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This, in turn, is regulated by the capacity of resistance arterial vessels to dilate during muscle contractions, for which nitric oxide (NO) generated by increases in blood flow and shear stress [25] is a requirement [10] , [28] . Patients with peripheral vascular disease have decreased levels of systemic nitric oxide [5] and impaired endothelial‐dependent dilation of both conduit [45] and resistance vessels [18] , [29] . In rat hindlimb muscles, acute ischemia attenuated endothelium‐dependent NO‐mediated vasodilation [41] , and chronic ischemia for 2 weeks following iliac artery ligation caused precapillary arterioles to lose their ability to dilate in response to muscle contractions [19] or to endothelial‐dependent vasoactive agents [23] .…”
mentioning
confidence: 99%